THE SHIFTING PATTERN OF G20 COUNTRIES' EXPORT PRODUCTS FROM 1994 TO 2024 - Akhmad Jayadi (PEOPLE: International Journal of Social Sciences, 2026)
The paper attempts to map and investigate the shifting pattern of G20 countries’ main export products classified by UNCTAD, i.e.: raw materials, intermediate goods, consumer goods, and capital goods. Data are obtained from UN COMTRADE (WITS World Bank) from 1994 to 2024 and separated into four ten-yearly view. The method used in this research is products mapping analysis that combine two tools, i.e.: Revealed Symmetric Comparative Advantage (RSCA) by Dalum, Laursen and Villumsen (1998) and Trade Balance Index (TBI) by Lafay (1992). The study predicts that the countries will be divided into three groups, i.e: linear pattern (from raw material to capital goods, or vice versa); non-linear pattern (random pattern); and consistent pattern (maintain the same goods in decades). This research will proof some international basic theories such as comparative advantage theory; H-O model; product cycles theory; demand structure hypothesis, and flying geese pattern.